ISO 9001:2015 QUALITY MANAGEMENT SYSTEM IN REALIZING SCHOOL CULTURE TRANSFORMATION AT SMKN 1 SURABAYA - Istiqomah, Nefis Faiqotul; Haq, Mohammad Syahidul; Karwanto; Nursalim, Mochamad; Khamidi, Amrozi; Amalia, Kaniati (International Journal of Cultural and Social Science, 2025)
Improving the quality of education is a primary requirement in the era of globalization and the Industrial Revolution 4.0. One strategic effort undertaken by schools is the implementation of the ISO 9001:2015 Quality Management System (QMS). This study aims to analyze the implementation of ISO 9001:2015 in realizing a quality culture transformation at SMK Negeri 1 Surabaya, focusing on the implementation of ISO principles, organizational culture changes, and supporting and inhibiting factors. This study used a descriptive qualitative approach through interviews, observation, and documentation. The results show that the implementation of ISO 9001:2015 at SMK Negeri 1 Surabaya was carried out systematically through quality policies, standard operating procedures (SOPs), internal audits, and management reviews. The principles of customer focus, leadership, and continuous improvement contributed significantly to improved school performance and the growth of a quality culture oriented towards accountability, openness, and continuous improvement. The transformation of organizational culture is evident in the increased quality awareness of the school community and cross-unit collaboration. Key success factors include visionary leadership, active participation of the school community, and support from industry partners, while obstacles include resistance to change and a lack of understanding of ISO principles. Overall, the implementation of ISO 9001:2015 at SMK Negeri 1 Surabaya has proven to be a significant catalyst in realizing the transformation of the school's quality culture. This system not only strengthens governance and managerial effectiveness but also changes the mindset of the school community to be more reflective, collaborative, and oriented towards sustainable quality. This research implies that strengthening human resource competencies and leadership commitment are key to the successful implementation of an ISO-based quality system in vocational education units.